Teacher development centres as a support strategy for the professional development of primary school teachers in Malawi - Banda, Grace Mkandawire (2012)
This thesis is about the influence of the teacher development centres (TDCs) as a support strategy for the professional development (PD) of primary school teachers in Malawi. PD of teachers is becoming an integral part of educational reforms in many countries. However, supporting and sustaining PD especially in poor countries is quite challenging. Many countries have adopted the use of teacher centres (TCs) as a support strategy for the PD of teachers and the TDCs in Malawi are an adaptation of the TCs from developed countries such as Britain where the concept of TCs was first hatched.